2009
DOI: 10.1603/022.038.0420
|View full text |Cite
|
Sign up to set email alerts
|

Field Efficacy of Entomopathogenic Fungi and Nematodes Targeting Caged Last-Instar Plum Curculio (Coleoptera: Curculionidae) in Michigan Cherry and Apple Orchards

Abstract: The plum curculio (Conotrachelus nenuphar Herbst) is a key pest of pome and stone fruit in eastern North America. We tested the efficacy of five pathogens over the course of three seasons in 10 Michigan apple and cherry orchards, with introductions of larvae to caged pots containing pathogen-treated soil. The nematode Steinernema riobrave was the most effective pathogen in the 2 yr it was tested, but only in soils with the highest sand content (81-88%) and when it was applied 1 h or 5 d after last instars of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Predation studies in the field and the laboratory provide evidence that biocontrol is an important component of pest management for orchard systems [ 16 ]. In addition, entomopathogenic fungi and nematodes show efficacy for biocontrol of apple pests [ 31 , 32 ]. However, little is known about the food webs in these systems and our data provide much needed information on elucidating this important aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Predation studies in the field and the laboratory provide evidence that biocontrol is an important component of pest management for orchard systems [ 16 ]. In addition, entomopathogenic fungi and nematodes show efficacy for biocontrol of apple pests [ 31 , 32 ]. However, little is known about the food webs in these systems and our data provide much needed information on elucidating this important aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate (60–80%) to high (>80%) mortality of weevils such as C. nenuphar , C. caryae , C. elephas and C. nucum was obtained after treatment with virulent isolates [ 209 , 210 , 211 , 212 ], Mycotrol ® and Naturalis ® [ 213 , 214 , 215 ] but only low (<60%) to moderate (60–80%) levels of control were achieved when adult weevils or larvae (e.g., C. caryae ) were introduced four days after EPF application [ 208 , 216 ]. Low to moderate mortality of C. caryae [ 204 , 217 , 218 ], C. sikkimensis [ 206 , 207 ], C. nucum [ 219 ] and C. nenuphar [ 220 ] was also achieved in the field after the application of virulent EPF isolates or commercial products (Beaupro ® , Metapro ® and Botanigard ® ), suggesting that the weevils moved onto the ground several days after fungal application [ 208 , 216 ]. To mitigate poor infectivity of EPF in the field, Shapiro-Ilan and Brown [ 215 ] suggested that using earthworms ( Lumbricus terrestris ) as phoretic hosts for B. bassiana in the soil could improve fungal infectivity in comparison to the more traditional applications of EPF directly to the topsoil.…”
Section: Effect Of Fungal Entomopathogens On Weevils With Life Cycmentioning
confidence: 99%
“…It is difficult to draw direct comparisons between EPF and EPNs because their mode of action and their effective concentrations are different. Studies show that when EPF or EPNs are applied on the topsoil before introducing weevil larvae, the EPNs provide better control of both C. caryae [ 226 ] and C. nenuphar [ 220 ] compared to EPF. However, when larvae are immersed in the fungal suspension and compared with EPNs (applied on the topsoil), the mortality of both C. elephas [ 227 ] and C. nenuphar [ 203 ] caused by EPF was always higher than that caused by EPNs.…”
Section: Effect Of Fungal Entomopathogens On Weevils With Life Cycmentioning
confidence: 99%
“…Cohn, 1872, Serratia sp. Bizio, 1823) (Shah & Pell, ; Ansari et al ., ; Lacey & Shapiro‐Ilan, ; Jackson & Jaronski, ; Pereault et al ., ). However, this strategy has some limitations, such as entomopathogenic and microbial products being unable to reach the target pest in the soil, as well as the failure of most applied microbes to survive in the soil environment (Jackson, ).…”
Section: Introductionmentioning
confidence: 97%